Q: How do you solve the equation 3x-2 equals 2x plus 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Calculus

Yes. (Assuming that -3x2 is the best representation of 3x2 that this browser will allow.)

3x2+x-4 = 0 (3x+4)(x-1) = 0 Solutions: x = 1 and x = -4/3 By using the quadratic equation formula.

y2-3x2+6x+6y= 18 is in standard form. The vertex form would be (y+3)2/24 - (x-1)2/8 = 1

Differentiate the function with respect to x: d/dx (x3 - 2x2 - 5x + 6) = 3x2 - 4x - 5 Set this derivative = 0 and solve. 3x2 - 4x - 5 = 0 implies that x = -0.7863 or 2.1196 (to 4 dp)

3x2 - 10x - 8 = (3x + 2) (x - 4)

Related questions

3x2 + 17x + c = 0, rearranging gives c = -3x2 - 17x

Set the equation equal to zero. 3x2 - x = -1 3x2 - x + 1 = 0 The equation is quadratic, but can not be factored. Use the quadratic equation.

x=-.25.

y2=x3+3x2

56

2

No. Y=3X2+1 is a Binomial Equation.

It has one double solution.

If you mean 3x2-7x+x = -4 then there are no solutions because the discriminant of the quadratic equation is less than zero.

2x^2 + 8x + 3 = 0

(a) y = -3x + 1

x2-5-4x2+3x = 0 -3x2+3x-5 = 0 or as 3x2-3x+5 = 0